Synthesis and thermoelectric properties of Ba2TiFeO6 double perovskite with insight into the crystal structure - Sri Gyan D.; Dwivedi A.; Roy P.; Maiti T. (My University, 2025)
Here we report the development of environment-friendly, non-toxic, single-phase Ba2TiFeO6 (BTF) double perovskite fabricated by solid-state synthesis route to evaluate its thermoelectric properties. XRD patterns and SEM micrographs confirmed phase purity and dense microstructure of ceramic sample. The crystal structure of BTF ceramic was confirmed to be hexagonal with P63/mmc space group by Rietveld Refinement of powder XRD data. Conduction mechanism of BTF double perovskite was analyzed by small polaron hopping and variable range hopping in correlation with the defect chemistry of this complex oxide. The maximum thermopower 412 µV/K was obtained at 1073 K in this material. The complex plane impedance spectroscopic analysis showed the disappearance of resistance contribution from grain boundaries and very negligible resistance due to grains above 400 K making it highly conductive. © 2018, © 2018 Taylor & Francis Group, LLC.